Uncommon Fistulous Complications in Pancreatitis: Rare Radiological Findings - Banerjee, Somya Nath; Azhagarasan, Ashwin Kumar; Vignesh, Vettri (Journal of Neonatal Surgery, 2025)
Background: Fistulous complications arising from pancreatitis are uncommon but can lead to significant diagnostic and therapeutic challenges. These abnormal communications with adjacent organs result from enzymatic tissue destruction, necrosis, or chronic inflammation. Objective: To present a case series of rare pancreatitis-associated fistulas—choledochogastric, pancreaticocolonic, and pancreaticopleural—and to highlight their diverse radiological findings, diagnostic difficulties and clinical presentations. Methods: Three patients with a history of acute or chronic pancreatitis presented with non-specific symptoms including abdominal pain, diarrhea, respiratory complaints, and fever. Multimodality imaging—CT, MRCP, DWI, and transhepatic cholangiography—was employed to identify and characterize the fistulous tracts. Results: Case 1: A choledochogastric fistula was diagnosed in a post-Frey’s procedure patient with persistent abdominal pain and fever. Cholangiography revealed communication between the hepatic duct and the gastric antrum. Case 2: A pancreaticocolonic fistula was identified in a patient with interstitial pancreatitis presenting with diarrhea. CT and diffusion-weighted imaging showed colonic communication with an inflammatory collection. Case 3: A pancreaticopleural fistula was found in a patient with necrotizing pancreatitis and respiratory symptoms. Imaging demonstrated extension of air-fluid levels through the esophageal hiatus into the pleural cavity. Conclusion: Pancreatitis-related fistulas are rare but clinically significant complications with varied and often misleading presentations. High clinical suspicion, supported by advanced imaging, is essential for timely diagnosis. Management should be tailored to the fistula’s location, severity, and associated complications, emphasizing a multidisciplinary approach to optimize outcomes